2023
DOI: 10.1039/d3se00435j
|View full text |Cite
|
Sign up to set email alerts
|

An efficient approach for controlling the crystallization, strain, and defects of the perovskite film in hybrid perovskite solar cells through antisolvent engineering

Abstract: Antisolvent engineering with the octylammonium salt OABr improves the quality of the perovskite film and suppresses nonradiative losses by 43.6%, resulting in high performance and stable inverted perovskite solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 90 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Previous computational studies have reported that such compressive strain can enhance the coupling between Sn-p (or Pb-p) and I-s orbitals, thereby elevating the valence band maximum in energy and shifting trap states into the bands. Consequently, the bandgap may decrease, and the trap states could be eliminated. , This compressive strain may result from the volume change and the pace of film formation during the application of the blended antisolvent. Furthermore, we analyzed the full width at half-maximum (FWHM) of the (110) peak, as shown in Figure b. A narrower FWHM signifies superior crystallinity, i.e., fewer defects and less strains within the crystal lattice.…”
Section: Resultsmentioning
confidence: 99%
“…Previous computational studies have reported that such compressive strain can enhance the coupling between Sn-p (or Pb-p) and I-s orbitals, thereby elevating the valence band maximum in energy and shifting trap states into the bands. Consequently, the bandgap may decrease, and the trap states could be eliminated. , This compressive strain may result from the volume change and the pace of film formation during the application of the blended antisolvent. Furthermore, we analyzed the full width at half-maximum (FWHM) of the (110) peak, as shown in Figure b. A narrower FWHM signifies superior crystallinity, i.e., fewer defects and less strains within the crystal lattice.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the solvents frequently employed to prepare perovskite solutions, particularly DMF, could potentially have detrimental impacts on people's health. Furthermore, by rapidly eliminating the host solvent, antisolvents are frequently utilized to promote the nucleation and crystallization of perovskite films [23,24]. However, the antisolvents that are widely utilized are extremely volatile and hazardous.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that morphological changes in perovskite thin films will change water-based degradation. We acknowledge that the film formation kinetics and resulting morphology will be altered with the use of an antisolvent bath. To keep the film formation kinetics reasonably similar to the control, the initial tension in the perovskite film was manipulated by using a substrate with a different CTE while using a film formation method identical to that used with glass (Figure A).…”
mentioning
confidence: 99%